Penyelesaian Sengketa Perceraian pada Era Modernisasi: Kajian Prosedur Arbitrase dalam Hukum Islam - Abdullah, Hanif; Muhtadin, Sabilul (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
This study focuses on the resolution of divorce conflicts in the modernization era by analyzing arbitration procedures in Islamic law. In light of swift social, cultural, and technological transformations, traditional dispute resolution methods, including divorce, encounter fresh obstacles. Through an examination of existing literature, this research delves into how arbitration, as an alternative dispute resolution mechanism, can be integrated within the Islamic legal framework to tackle divorce conflicts in contemporary times. The analysis underscores the significance of adjusting Islamic legal mechanisms to present-day circumstances while upholding core principles of justice, fairness, and empathy. It deliberates on the role of arbitration in offering a methodical and culturally attuned approach to settling divorce disagreements, taking into consideration factors such as accessibility, gender dynamics, and technological progress. This academic scrutiny offers insights into the potential of arbitration in fostering equity and safeguarding the rights of women and children involved in divorce proceedings. The results emphasize the necessity for further investigation and interdisciplinary cooperation to improve the efficiency and accessibility of arbitration procedures in handling divorce disputes across varied cultural settings.